Performance of Intergrowth 21st Growth Charts in the Diagnosis of Small and Large for Gestational Age in Term and Preterm Newborns - Marques, Bárbara (2020)
Introduction: Birth weight is a major contributor to neonatal morbidity and mortality and is associated with chronic diseases in adulthood. This study aimed to evaluate the use of Intergrowth 21st instead of the Fenton & Kim 2013 growth charts in the diagnosis of small and large for gestational age in a group of Portuguese newborns.Material and Methods: We conducted an analytical and retrospective study to evaluate birth weight of term and preterm newborns using both growth charts. Groups studied: ‘Term-weeks’ and ‘Term-days’ (term newborns with gestational age in weeks and days, respectively), ‘Preterm-weeks’ and ‘Preterm-days’ (preterm newborns with gestational age in weeks and days, respectively).Results: A total of 14 056 newborns were included, 6% preterm. Using the Intergrowth 21st growth charts, the groups ‘Term-weeks’ (n = 12 081), ‘Term-days’ (n = 1118), ‘Preterm-weeks’ (n = 617) and ‘Preterm-days’ (n = 240), classified as small for gestational age according to the Fenton & Kim 2013 growth charts were adequate for gestational age in 52.8%, 57.8%, 37.7% and 9.3% respectively; and 9.2%, 9.2%, 5.9% and 0.6% of adequate for gestational age newborns were large for gestational age, respectively. In the ‘Pretermdays’ group, 7.9% of adequate for gestational age newborns were small for gestational age and 22.2% of large for gestational age newborns were adequate for gestational age, all with gestational age below 231 days.Discussion: The use of the Intergrowth 21st growth charts in this sample resulted in a lower number of newborns being classified as small for gestational age, except in very preterm newborns.Conclusion: Considering the results obtained, we suggest that Portuguese maternity hospitals use the Intergrowth 21st instead of the Fenton & Kim 2013 growth charts. However, more studies are needed to confirm these results.